Creation of Enterprises Formation of Entrepreneurs Training Planning for Micro, Small and Medium Enterprises - Sukmana, Cucu; Hatimah, Ihat; Wahyudin, Uyu; Akhyadi, Ade Sadikin (Journal of Nonformal Education, 2022)
This study aims to provide a study by describing the CEFE training plan in perfecting the entrepreneurship training program. The research method used is a qualitative approach with an Emic view. The research subjects are MSME actors, 30 respondents, 3 MSME assistants, and 1 coordinator who has successfully implemented the training program. This sampling was carried out by considering one of the reasons (Purposive Sampling), then data collection involved MSME actors, assistants and coordinators as well as data collection tools by means of observation, documentation, interviews. Based on the research results, the MSME Program through the CEFE training is a comprehensive training instrument using an action-oriented and experiential/experience-based learning approach in sharing and improving business management and personal competence by using a broad target group, especially in the context of increasing income and employment. work. work. work. employment opportunities and their contribution to economic development in Cimahi City, West Java Province, it was found that the CEFE training management plan was very helpful in managing training management and in particular for dealing with problems in the business world. The training model that is carried out is more structured and focused when compared to not applying the model. In this training, management applies a real simulation in the entrepreneurial world which makes this model very suitable to be applied. The impact of this research is to develop entrepreneurship and apply the CEFE model so that it can be applied in the implementation of training programs.